O Camiño de Santiago na pintura de Antonio Moragón - Moragón Arias, María Pilar (Madrygal. Revista de Estudios Gallegos, 2009)
In this article we are going to describe the work of Antonio Moragón Agudo, the first painter in the twentieh century that portraited the landscapes of the “ruta xacobea” across several exhibitions and publications.